Graha Maria Annai Velangkanni, Medan, Sebagai Gereja Pewarta Studi Kasus di Gereja Velangkanni di Keuskupan Agung Medan - Sianturi, Berkat Rahmat (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2019)
The article is focusing its analysis on the Graha Maria Annai Velangkanni Church (the Our Lady of Good Health Church) in Medan, North Sumatra. The church describes and introduces itself as ‘Gereja Pewarta’ (an Evangelizing Church). At first sight, however, this Catholic church gives an impression of a Buddhist or Hindu temple, due to its construction. But it is rich in and full of traditional Catholic symbols. It presents itself in two meanings, viz., as the people of God and the sacred place for worship. The popularly called Velangkanni Church in the Archdiocese of Medan with all its richness, basically wants to proclaim Jesus Christ and to promote the devotion to the Blessed Virgin Mary, not merely a place of prayer or worship.